2022
DOI: 10.1111/jppi.12416
|View full text |Cite
|
Sign up to set email alerts
|

As far as possible: The relationship between public awareness, social distance, and stigma towards people with intellectual disability

Abstract: Research shows that people with intellectual disability (ID) face public stigma. However, a recently published narrative review suggests that this phenomenon has not been explored in a Latin American country. This study fills the gap in our understanding of public stigma towards people with intellectual disability in Chile. 395 adults from the general population (18 to 78 years) participated in the survey. Using the Intellectual Disability Literacy Scale, adapted for Chile, we explored the participants' litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…For instance, in a sample of adults with ID in the United Kingdom, Emerson (2010) found that the consequences of bullying and disablism were more pronounced among individuals with lower levels of material or social resources. Additionally, Tenorio et al (2022) showed that in Chile lay people from higher socioeconomic backgrounds expressed greater stigma toward persons with intellectual disabilities. These studies indicate a relationship between socioeconomic status and stigma, which is perceived by adults with intellectual disability.…”
Section: Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a sample of adults with ID in the United Kingdom, Emerson (2010) found that the consequences of bullying and disablism were more pronounced among individuals with lower levels of material or social resources. Additionally, Tenorio et al (2022) showed that in Chile lay people from higher socioeconomic backgrounds expressed greater stigma toward persons with intellectual disabilities. These studies indicate a relationship between socioeconomic status and stigma, which is perceived by adults with intellectual disability.…”
Section: Itemsmentioning
confidence: 99%
“…This might be explained in two ways: (1) actual experience of stigma might be low, or (2) Chilean adolescents have low awareness of stigmatization and because of this, they exhibit low levels of self-perceived stigma. A recent study on public stigma in Chile (Tenorio et al, 2022) showed that Chilean lay people tend to have stigmatizing beliefs and negative behaviors toward people with intellectual disability.…”
Section: Itemsmentioning
confidence: 99%